Enhancing Operational Efficiency In Cross-docking Warehouses Through Value Stream Mapping - Nofrisel, Nofrisel; Pratiwi, Sekar Widyastuti; Fahriansyah, Ahmad; Juhri, Apsada (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2025)
This study aims to identify waste and analyze process improvements in the sorting area of a cross-docking warehouse at PT X, a logistics service company. The research applies the Value Stream Mapping (VSM) method as a tool within lean management to evaluate operational processes and identify activities that do not provide added value. Data were collected through direct observation of sorting activities, documentation of operational processes, and analysis of process duration within the warehouse. The results show that several operational activities still contain waste, particularly waiting time caused by delays in goods arrival and inefficiencies in sorting operations due to limited sorting space. The current state map indicates that the average sorting duration reaches 199 minutes per sorting code. After implementing improvements such as sorting area reorganization, establishing Key Performance Indicators (KPI), and optimizing labor allocation, the proposed future state map reduces the average sorting duration to 85.25 minutes per sorting code. The findings indicate that implementing Value Stream Mapping can significantly improve operational efficiency in cross-docking warehouse processes by reducing non-value-added activities and optimizing workflow.